Figure 46 from: Saarela JM, Sokoloff PC, Gillespie LJ, Bull RD, Bennett BA, Ponomarenko S (2020) Vascular plants of Victoria Island (Northwest Territories and Nunavut, Canada): a specimen-based study of an Arctic flora. PhytoKeys 141: 1-330. https://doi.org/10.3897/phytokeys.141.48810 - Saarela, Jeffery M.; Sokoloff, Paul C.; Gillespie, Lynn J.; Bull, Roger D.; Bennett, Bruce A.; Ponomarenko, Serguei (Zenodo, 2022)
Figure 46 ASalix arctica pistillate catkins, Gillespie et al. 7484BSalix glauca var. stipulata pistillate catkins, Gillespie et al. 8038CSalix glauca var. stipulata habit, Gillespie et al. 8038DSalix polaris habit, Gillespie et al. 9991ESalix polaris pistillate catkins, Gillespie et al. 9991FSalix reticulata habit, Gillespie et al. 7475GSalix richardsonii habitat, Johansen Bay, NU, 15 July 2008. Photos A, F by R.D. Bull and B, C–E, G by L.J. Gillespie.